HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN PERILAKU PERGAULAN BEBAS MAHASISWA DI SEMARANG - Agatha Alfadiazti; Wigyo susanto; Dwi Heppy Rochmawati (Journal of Medical Practice and Research, 2025)
Free social behavior among university students represents a complex social phenomenon influenced by the interaction between individual characteristics and immediate environmental factors, particularly the family as a primary support system. This study aimed to examine the relationship between family support and free social behavior among university students in Semarang. A quantitative correlational field study with a cross-sectional design was conducted among undergraduate students of the Faculty of Nursing at Sultan Agung Islamic University, Semarang. A total of 100 students were selected using purposive sampling from a population of 143 students. Data were collected using standardized questionnaires measuring family support and free social behavior, both of which demonstrated satisfactory validity and high reliability. Data analysis was performed using cross-tabulation and Spearman Rank correlation to determine the strength and direction of the association between variables. The results revealed a strong and statistically significant negative correlation between family support and free social behavior, indicating that higher levels of family support were associated with lower engagement in free social behavior. These findings emphasize the critical role of family support as a protective factor in shaping adaptive and responsible social behavior among university students, despite increasing independence and complex social environments.